Most Common Sexually Transmitted Infections in LGBT - Baiq Henny Salim Alawiyah; Alfia Mawaddah; Annisa Diyanabila Indrasari; Ayundha Rizky Lestari; Diki Wahyudi; Fatikha Rudia Ahda; I Gede Aditya Satrya Bhuwana Cakra; Ni Made Ayu Shinta Dewi; Rida Dwi Arista; Puji Widyastuti; Talitha Syahla; Vanessa Essianda; Yunita Hapsari (Jurnal Biologi Tropis, 2023)
Sexually Transmitted Infections (STIs) are infections that are transmitted through sexual contact with an infected partner through vaginal, oral and anal sex. STIs can also be transmitted from mother to child during pregnancy, childbirth, and breastfeeding. LGBT is a group at high risk of contracting STIs, especially syphilis. Syphilis rates increased every year by 28.6% from 2020 to 2021. LGBT people accounted for 47% (18,381) of syphilis cases and (44%) LGBT people who had syphilis also had HIV. This article was written with the aim of finding out more about the molecular biology, phatophysiology and clinical symptoms of syphilis. The method used is a literature review on the NCBI website, Google Scholar, and Research Gate. It can be concluded that syphilis can be cured in the early stages of infection, but if adequate treatment is not received it can become a systemic infection and progress to the latent phase. Syphilis can also increase the risk of transmitting HIV which cannot be cured but can take medication to treat the symptoms. In conclusion, LGBT is a group at high risk of contracting STIs. The reason is, they have different sexual lives in general. The sexual activities carried out are anal sex, oral sex and variations thereof. Anal sex has a potential risk of injury to the anus. Because the anus is not elastic, sexual intercourse carries a risk of injury, so syphilis is more easily transmitted if there is damage to the anal area.